2022
DOI: 10.1186/s13595-022-01167-3
|View full text |Cite
|
Sign up to set email alerts
|

Interpolated daily temperature and precipitation data for Level II ICP Forests plots in Germany

Abstract: Key message: A harmonized, comprehensive meteorological time series for 78 German intensive forest monitoring plots (Level II) has been made available from 1961 to 2019. The used hybrid spatial interpolation routine using simple linear regression and inverse distance weighting allows for gap filling of missing data and also for extrapolation outside measurement period to analyze long-term effects of climate on forest ecosystems. The dataset is available at https://www.openagrar.de/receive/openagrar_mods_000791… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
0
0
Order By: Relevance
“…We found that all the variables were normally distributed. Simple linear regression involves modeling the relationship between two variables, namely the independent and dependent variables [52]. It is utilized to approximate the dependent variable through the use of the best-fit line.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…We found that all the variables were normally distributed. Simple linear regression involves modeling the relationship between two variables, namely the independent and dependent variables [52]. It is utilized to approximate the dependent variable through the use of the best-fit line.…”
Section: Statistical Analysesmentioning
confidence: 99%